Creation in Ancient Elam based on Royal Elamite Inscriptions and Rock Reliefs - DADASHI, Iraj; JAHANGIRFAR, Milad; SEYYED AHMADI ZAVIEH, Saeed (Historia i Świat, 2023)
Royal Elamite inscriptions offer valuable insights into a range of themes related to ancient Iran. However, to date, no Elamite creation myth has been recovered. Nonetheless, there exist indirect references in the inscriptions and rock reliefs that can be used to reconstruct such an account. This study aims to partially reconstruct the Elamite genesis by examining the linguistic and iconographical clues. It is important to note, however, that this primary investigation provides only limited insights into the creation myth in ancient Elam.